PENGARUH BRAND AMBASSADOR, ELECTRONIC WORD OF MOUTH, DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA PENGGUNA MARKETPLACE TOKOPEDIA DI MAGETAN) - Rizka Dwi Lestari; Umi Farida; Titis Purwaningrum (Jurnal Cakrawala Ilmiah, 2023)
This study aims to analyze the influence of brand ambassadors, electronic word of mouth, and product diversity on purchasing decisions among users of the Tokopedia marketplace in Magetan. The research method used is a quantitative method. The sample in this study was 100 respondents using a purposive sampling technique. Data collection teqniques throught distributing questionnaires or questionnaires online on the google form using a likert scale. The result of this study indicate that brand ambassadors have no significant effect on purchasing decision for Tokopedia marketplace users in Magetan, electronic word of mouth has a significant effect on purchasing decisions for Tokopedia marketplace users in Magetan. There is a significant influence of brand ambassadors, electronic word of mouth, and product diversity simultaneously on purchasing decision for users of the Tokopedia marketplace in Magetan.